USABILITY TESTING ANALYSIS ON PROFESSIONAL SOCIAL MEDIA USING THE SYSTEM USABILITY SCALE (SUS) METHOD - Fenny Purwani; fatikah aulia farhah (Indragiri Islamic University, 2024)
Usability is a critical aspect of digital product design, which determines how effective, efficient, and satisfying a product is for its users. This research aims to evaluate the level of usability of digital applications in a professional context using the System Usability Scale (SUS) method. The SUS method was chosen for its ability to provide a quick and accurate assessment of the usability of a product or service. The test results show that the average SUS score of the respondents is 63, which is below the general average of 68. This score indicates that the tested digital product has a poor level of usability and requires improvement to increase user satisfaction.